2014
DOI: 10.3389/fenvs.2014.00009
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal pollution in Guangdong Province, China, and the strategies to manage the situation

Abstract: Guangdong Province in China runs a risk of gradually increasing pollution of its agricultural land and, as a consequence, toxic agricultural products. We concentrate here on the situation for cadmium, copper, and lead. For these metals we describe the toxicology, the current pollution and its sources, and what can be done to improve the situation by cleaning the soil from pollutants, by choice of crops that allocate a minimum of the metals to edible parts, and by switching to non-food crops when other measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 140 publications
1
26
0
Order By: Relevance
“…Since they are not biodegradable, they are prone to accumulate. Some heavy metals are carcinogenic, mutagenic, teratogenic and endocrine disruptors while others cause neurological and behavioral changes especially in children [1,2]. Due to their ubiquitous nature, they are often present in wastewater and their effective removal to acceptable levels commonly requires the use of adsorbents.…”
Section: Introductionmentioning
confidence: 99%
“…Since they are not biodegradable, they are prone to accumulate. Some heavy metals are carcinogenic, mutagenic, teratogenic and endocrine disruptors while others cause neurological and behavioral changes especially in children [1,2]. Due to their ubiquitous nature, they are often present in wastewater and their effective removal to acceptable levels commonly requires the use of adsorbents.…”
Section: Introductionmentioning
confidence: 99%
“…In the past 5 decades, rice production in China has more than tripled, mainly due to increased grain yield. Meanwhile, the overuse of nitrogen and phosphorus fertilizers as well as pesticides in rice production has induced serious challenges regarding water and soil pollution (1), calling for an urgent need to develop a "green" rice production system that can replace the conventional intensive cultivation system without a yield reduction.…”
mentioning
confidence: 99%
“…We found that Fe and Zn might possibly come from mining and smelting activities. In general, mining and smelting were the main anthropogenic sources of Fe and Zn contamination in river water [20]. There were numerous mining and smelting factories in Guangdong Province, especially in the northern part of the province where many rivers and streams (e.g., the Pearl River) originated [20].…”
Section: Possible Source Identification Of Pollutants In Subtropical mentioning
confidence: 99%
“…In general, mining and smelting were the main anthropogenic sources of Fe and Zn contamination in river water [20]. There were numerous mining and smelting factories in Guangdong Province, especially in the northern part of the province where many rivers and streams (e.g., the Pearl River) originated [20]. Two highly toxic metals (Hg and Cd) might mainly come from various industrial sources including electronic factories, industrial boilers, power plants and cement plants [45].…”
Section: Possible Source Identification Of Pollutants In Subtropical mentioning
confidence: 99%
See 1 more Smart Citation